PRINCIPAL MANAGERIAL COMPETENCE, SCHOOL CULTURE, AND TEACHER JOB SATISFACTION IN BAGUALA - Sentia Latusuay; Izaak Hendrik Wenno; Tanwey Gerson Ratumanan; Lamberthus Johanes Lokollo (SOSIOEDUKASI, 2026)
This study examined the influence of principal managerial competence and school culture on teacher job satisfaction in senior high schools in Baguala District, Ambon. A quantitative associative design was used to test partial and simultaneous effects among the variables. The respondents were 116 teachers selected proportionally from five senior high schools: SMAN 14 Ambon, SMAN 5 Ambon, SMAN 9 Ambon, SMAN Siwalima Ambon, and SMA Kristen Passo. Data were collected through a Likert-scale questionnaire measuring principal managerial competence, school culture, and teacher job satisfaction. The instruments were valid and reliable, with Cronbach’s Alpha values of 0.912, 0.894, and 0.901 respectively. Data were analyzed using descriptive statistics, classical assumption tests, simple regression, and multiple linear regression with SPSS 25. The findings show that principal managerial competence had a positive and significant effect on teacher job satisfaction (t = 6.214; p < 0.05), and school culture also had a positive and significant effect (t = 5.876; p < 0.05). Simultaneously, both variables significantly affected teacher job satisfaction (F = 38.624; p < 0.05), explaining 57.2% of its variance. The study concludes that effective school management and a positive school culture are important determinants of teacher job satisfaction.